2013
DOI: 10.3390/molecules181215094
|View full text |Cite
|
Sign up to set email alerts
|

Maternal High Fat Feeding Does Not Have Long-Lasting Effects on Body Composition and Bone Health in Female and Male Wistar Rat Offspring at Young Adulthood

Abstract: High fat diets adversely affect body composition, bone mineral and strength, and alter bone fatty acid composition. It is unclear if maternal high fat (HF) feeding permanently alters offspring body composition and bone health. Female rats were fed control (CON) or HF diet for 10 weeks, bred, and continued their diets throughout pregnancy and lactation. Male and female offspring were studied at weaning and 3 months, following consumption of CON diet. At weaning, but not 3 months of age, male and female offsprin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 29 publications
2
26
0
1
Order By: Relevance
“…In offspring most of the studies have shown that prenatal exposure to an HF diet increases birth weight and weight gain in postnatal days. In this study, a decrease in food and energy intakes as well as body weight, which was observed in HF offspring, could be the result of changes in feeding regulatory centers programming or switching from the HF to a control diet (Miotto et al, 2013). Since HF offspring are exposed to high level of dams' corticosterone during critical period of life, their HPA axis programmings might be affected and cause a lower level of plasma corticosterone in adulthood.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…In offspring most of the studies have shown that prenatal exposure to an HF diet increases birth weight and weight gain in postnatal days. In this study, a decrease in food and energy intakes as well as body weight, which was observed in HF offspring, could be the result of changes in feeding regulatory centers programming or switching from the HF to a control diet (Miotto et al, 2013). Since HF offspring are exposed to high level of dams' corticosterone during critical period of life, their HPA axis programmings might be affected and cause a lower level of plasma corticosterone in adulthood.…”
Section: Resultsmentioning
confidence: 97%
“…Also reported are an impaired glucose tolerance and increased fasting insulin, associated with higher (Desai et al, 2014) or normal (Jacobs et al, 2014) fasting glucose concentrations. Moreover, some studies showed that HF diet consumption in rats (Cerf et al, 2012) or mice (Tuohetimulati et al, 2012) in pregnancy and lactation periods resulted in glucose intolerance and increased the homeostasis model assessment of insulin resistance (HOMA-IR) index (Cerf et al, 2012;Miotto et al, 2013) in offspring. The issue of the impact of maternal HF diet consumption on glucose homeostasis in both mother and offspring has attracted much attention and needs to be further clarified.…”
Section: Introductionmentioning
confidence: 99%
“…There is accumulating evidence supporting that perinatal overnutrition or high-fat diet (HFD) consumption induces health problems in adult offspring, such as the metabolic syndrome, hypertension and cardiovascular dysfunction (Khan et al 2004, Alfaradhi & Ozanne 2011. Nevertheless, other studies have also reported that adult offspring of HFD-fed dams can have normal glucose tolerance and body composition (Miotto et al 2013, Platt et al 2014. More specifically, although numerous studies have indicated the cerebrovascular hazards of an increased intake of dietary fat in adults (Langdon et al 2011) or beginning in childhood (Deutsch et al 2009), it remains to be established whether HFD consumption during pregnancy and the suckling period can influence the cerebrovascular health of adult offspring.…”
Section: Introductionmentioning
confidence: 99%
“…Bone fatty acid composition is altered by the type and amount of fatty acids consumed in developing rodents [1][2][3][4][5]. Specifically, high saturated fatty acid (SFA) diets (10-20 % SFA source by weight fed for 9-17 weeks) result in lower amounts of n-3 polyunsaturated fatty acids (PUFA) or n-6 PUFA in the femur [1,2] and alveolar bone [4] of developing male and female rats.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, high saturated fatty acid (SFA) diets (10-20 % SFA source by weight fed for 9-17 weeks) result in lower amounts of n-3 polyunsaturated fatty acids (PUFA) or n-6 PUFA in the femur [1,2] and alveolar bone [4] of developing male and female rats. However, high SFA diets that are thought to alter bone total lipid composition have either no effect [1] or a negative effect [6] on bone mineral content and/or density in 7-15 week old male and female rats.…”
Section: Introductionmentioning
confidence: 99%